Capacidad reproductiva de hembras de spodoptera frugiperda provenientes de larvas tratadas con altas dosis de cipermetrina y deltametrina - Barragán averos, Rocío (2011)
This research was conducted at the experimental farm "San Pablo", Faculty of Agricultural Sciences at the Technical University of Babahoyo and its surroundings. The same is located at Km 7 ½ Montalvo - Babahoyo way, were the observations and data collection in the Entomology Laboratory located in the Faculty, in order to determine the effect on the reproductive capacity of females of Spodoptera frugiperda whose larvae were exposed to the use of Cypermethrin and Deltamethrin. To obtain larvae proceeded as follows, was taken in the process of developing larvae, it took them to the lab and complete their life cycle was obtained for egg masses and start the job. The larvae hatch when the vessels were separated into individual pieces were given tender leaves of maize for food, providing adequate moisture with pieces of cotton wool moistened with distilled water until they reached the third instar, where we proceeded to apply Deltamethrin dose of 12.5μg / larva and Cypermethrin at a dose of 50μg / larva